Cardiopulmonary Resuscitation With Mechanical Chest Compression Device During Percutaneous Coronary Intervention. A Case Report - Ujvárosy, Dóra; Sebestyén, Veronika; Ötvös, Tamás; Ratku, Balázs; Lorincz, István; Szuk, Tibor; Csanádi, Zoltán; Berényi, Ervin; Szabó, Zoltán (Frontiers in Cardiovascular Medicine, 2021)
Sudden cardiac death is a leading cause of death worldwide, whereby myocardial infarction is considered the most frequent underlying condition. Percutaneous coronary intervention (PCI) is an important component of post-resuscitation care, while uninterrupted high-quality chest compressions are key determinants in cardiopulmonary resuscitation (CPR). In our paper, we evaluate a case of a female patient who suffered aborted cardiac arrest due to myocardial infarction. The ambulance crew providing prehospital care for sudden cardiac arrest used a mechanical chest compression device during advanced CPR, which enabled them to deliver ongoing resuscitation during transfer to the PCI laboratory located 20 km away from the scene. Mechanical chest compressions were continued during the primary coronary intervention. The resuscitation, carried out for 2 hours and 35 minutes, and the coronary intervention were successful, as evidenced by the return of spontaneous circulation and by the fact that, after a short rehabilitation, the patient was discharged home with a favorable neurological outcome. Our case can serve as an example for the effective and safe use of a mechanical compression device during primary coronary intervention.